A longitudinal study of tapping to the beat by school-aged children with and without dyslexia: assessments of the mediating role of phonology - Flanagan, Sheila; Wilson, Angela M.; Gabrielczyk, Fiona C.; MacFarlane, Annabel; Feltham, Georgia; Mandke, Kanad; Goswami, Usha (Frontiers in Developmental Psychology, 2025)
In this article, we report a longitudinal study of the relationship between tapping consistency, phonological awareness, and literacy development in a sample of children initially aged approximately 8 years who were followed for 6 years. The sample comprised 121 participants, some of whom were diagnosed with developmental dyslexia (DYS, N = 58). The other typically developing children were either chronological-age-matched controls (CA, N = 30) for DYS, or reading-age-matched controls (RA, N = 33). The task was tapping to a 2-Hz beat, and the data were analyzed using circular statistics. This resulted in a vector for each child with two dependent variables, magnitude (length, between 0 and 1, often termed synchronization consistency) and phase (+/– π radians). The number of children able to synchronize (“synchronizers”) increased with age, and so did synchronization consistency. The number of “non-synchronizers”, children tapping at random, declined as the study progressed. Time-lagged relations between synchronization consistency and composite measures of phonological awareness and literacy were significant during the first 3 years of the study. They remained significant for the literacy composite as the children got older. All groups of children (DYS, CA, and RA) established a significant preferred tapping phase; however, time-lagged relations between the behavioral composites and phase measures were not significant at any time point. Mediation analysis and multiple regression analyses showed that tapping consistency significantly predicted later phonological awareness and that cross-sectional relations between rhythmic synchronization and literacy were mediated by phonology. The data are discussed in terms of temporal sampling theory.